Governance In Transition: A Content Analysis Of The Papua Barat Daya Regional Parliament Secretariat - Stanny Terianus Rumaseb; Ulul Albab; Sarwani Sarwani; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the institutional discourse and administrative practices of the Secretariat of the Regional People’s Representative Council (DPRD) in the newly established province of Southwest Papua, Indonesia. Utilizing a qualitative content analysis approach, the research analyzes a corpus of official documents produced between 2022 and 2025, with particular attention to how the principles of good governance—transparency, accountability, participation, and effectiveness—are reflected and operationalized in a transitional bureaucratic setting. The findings reveal that while procedural transparency and organizational effectiveness are relatively well-articulated in formal documents, mechanisms for accountability and citizen participation remain underdeveloped and largely symbolic. This indicates that the new administrative structures are still in the process of consolidating practices that meaningfully incorporate civic engagement. The study further identifies significant patterns of institutional isomorphism, wherein bureaucratic templates, legal frameworks, and administrative routines from older provincial governments are mimicked and reproduced. Although such imitation provides a sense of stability and legitimacy, it may come at the expense of local relevance and the incorporation of context-specific innovations. In particular, reliance on inherited bureaucratic models risks marginalizing indigenous governance traditions and community-driven practices that could enhance inclusivity and responsiveness. The analysis underscores the performative and symbolic dimensions of governance during periods of institutional formation, highlighting the tension between adopting established administrative norms and fostering context-sensitive practices tailored to the realities of frontier provinces. Methodologically, the study demonstrates the value of document analysis in capturing governance dynamics where field access is limited, politically sensitive, or constrained by security issues. The study concludes by offering practical recommendations: strengthening participatory frameworks to ensure more substantive public involvement, integrating indigenous governance values to enhance legitimacy, and designing flexible policy models that can adapt to the unique sociopolitical challenges of Southwest Papua. In doing so, the research contributes both to the broader scholarship on governance in post-conflict and frontier regions and to the practical debates on institutional development in Indonesia’s newest province.